(3GdHjGf GdeZQHs - (3eMeO GdeQGcTj, CHh YHO Gddg GdeYQha HGHf YPGQj,J (B695 (3g` s
(3ChdgG (B:s
(3GNJUGQ GdNHQ HMQcI JGTajf CHj GdLHd HQSe bJd GdehMOjf aNQL JGTajf ef eQGcT ai LeGOi GdChdi s
(3BNQgG (B:s
(3HMjK ebJd CHj OHhS SfI (B668 s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B95s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs